A multi-purpose polarization-maintaining optical fiber and a preparation method thereof

By reducing the thermal expansion coefficient and viscosity of the stress zone in the polarization-controlled fiber, and adopting the phosphorus-doped design of the inner and outer cladding, the problem of stress zone cracking during fiber grinding is solved, and the multi-purpose adaptation of optical fibers in the fields of fiber gyroscopes and fiber devices is achieved.

CN112305664BActive Publication Date: 2024-12-27JIANGSU FASTEN OPTOELECTRONICS TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202011117172.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-19
Publication Date
2024-12-27
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

Existing polarization-resistant fibers are prone to stress zone cracking in the grinding process, which makes them unable to be applied to fiber gyroscopes and fiber devices at the same time, affecting their birefringence performance and accuracy.

Method used

By reducing the thermal expansion coefficient and viscosity in the stress region of the optical fiber, the internal and external cladding doped phosphorus design is adopted, combined with gradient doping technology, the refractive index and thermal expansion coefficient of the stress region are adjusted, the internal stress and viscosity difference of the stress region are reduced, and the stress region is enhanced. Adaptability to cladding is suitable for a variety of process requirements.

Benefits of technology

It realizes the risk of stress zone cracking during fiber grinding without sacrificing birefringence performance, and is suitable for various uses of fiber gyroscopes and fiber devices, taking into account the process requirements of different applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112305664B_ABST
    Figure CN112305664B_ABST
Patent Text Reader

Abstract

The invention relates to a multi-purpose polarization-maintaining optical fiber and a preparation method thereof, and belongs to the technical field of polarization-maintaining optical fibers. The cross-sectional structure of the optical fiber is a core layer (1), an inner cladding layer (2), an outer cladding layer (3) and a coating layer from the inside to the outside, wherein the core layer (1) is germanium-doped quartz glass with a diameter of D1 and a refractive index of n1; the inner cladding layer (2) is phosphorus-doped quartz glass with a diameter of D2 and a refractive index of n2; the outer cladding layer (3) is phosphorus-doped quartz glass with a diameter of D3 and a refractive index of n3; two stress regions (4) are arranged in the inner cladding layer (2), with a diameter of D4, respectively, being boron-doped and fluorine-doped quartz glass, with a refractive index of n4, and the two stress regions (4) are symmetrically arranged on both sides of the core layer (1); the refractive index difference between the core layer (1) and the inner cladding layer (2) is n1-n2=0.005-0.020; the refractive index difference between the inner cladding layer (2) and the stress region (4) is n2-n4=0.008-0.015. The optical fiber can adapt to the grinding and taper processes in the field of optical fiber device manufacturing, and can also adapt to the ring winding process in the field of optical fiber gyroscope manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polarization-maintaining optical fiber, and in particular to a panda-type polarization-maintaining optical fiber and a preparation method thereof. Background Art

[0002] Polarization-maintaining fiber, also known as polarization-maintaining fiber, is used to transmit linearly polarized light. When a linearly polarized light is coupled into a polarization-maintaining fiber, if the polarization direction of the linearly polarized light coincides with the polarization axis of the polarization-maintaining fiber, the linearly polarized light can maintain its linear polarization direction during transmission until it leaves the polarization-maintaining fiber, which is the birefringence phenomenon of the polarization-maintaining fiber. There are many reasons for the birefringence of optical fibers. Both geometric and stress inhomogeneities can introduce birefringence. Stress birefringence polarization-maintaining fibers mainly include bowtie-type polarization-maintaining fibers, panda-type polarization-maintaining fibers, and elliptical cladding-type polarization-maintaining fibers.

[0003] It is widely used in various fields of the national economy, such as aerospace, aviation, navigation, industrial manufacturing technology and communications. In interferometric fiber sensors based on optical coherence detection, the use of polarization-maintaining fiber can ensure that the linear polarization direction remains unchanged and improve the coherent signal-to-noise ratio to achieve high-precision measurement of physical quantities. As a special type of optical fiber, polarization-maintaining fiber is mainly used in sensors such as fiber optic gyroscopes and fiber optic hydrophones, and fiber optic communication systems such as DWDM and EDFA. It is a special type of optical fiber with wide application value.

[0004] According to the application characteristics of polarization-maintaining fiber, it is mainly used in two major areas: one is the fiber optic gyroscope system, and the other is the polarization-maintaining fiber device. According to the different occasions of fiber use, the fiber also varies. When used in the fiber optic gyroscope system, the high birefringence fiber involved is mainly characterized by the large effective area of ​​the stress zone and the high concentration of boron doping, so as to ensure the high polarization crosstalk after the fiber is wound around. Correspondingly, when used in polarization-maintaining fiber devices, the process involves mechanical grinding of the fiber end face, which has certain requirements on the size of the stress zone of the polarization-maintaining fiber and the concentration of boron. The large effective area of ​​the stress zone and the high concentration of B doping will cause the stress zone and the cladding to crack during the grinding process. This is because although the high concentration of B doping can significantly reduce the relative refractive index of the stress zone, it will also cause the thermal expansion coefficient of the stress zone to be greatly increased compared with the cladding, which is easy to cause cracking at the interface during the grinding process. This leads to the fact that the optical fiber suitable for the fiber optic gyroscope system is often not suitable for the processing of optical fiber devices.

[0005] At present, domestic polarization-maintaining optical fiber for fiber optic gyroscopes has basically achieved domestic self-sufficiency, while the market capacity of polarization-maintaining optical fiber for devices is relatively small due to the above-mentioned process reasons. Domestic polarization-maintaining optical fiber for optical fiber devices still mainly relies on imported optical fibers.

[0006] Chinese patent CN103145349A discloses "a method for manufacturing low-stress polarization-maintaining optical fiber for coupling". The low-stress polarization-maintaining optical fiber is mainly processed by stripping the bare optical fiber part of the original polarization-maintaining optical fiber at the end, and by building a platform and applying an adhesive to reduce the deterioration of the extinction ratio caused by the stress of the adhesive on the polarization-maintaining optical fiber at high and low temperatures. The invention achieves low stress of the optical fiber by improving the post-processing method of the polarization-maintaining optical fiber, and does not involve changes to the optical fiber itself.

[0007] Chinese patent CN106291807A discloses "a crack-resistant panda-type polarization-maintaining optical fiber". This optical fiber mainly sets a refractive index gradient transition layer at the edge of the stress layer to decompose and release the stress at the edge of the stress layer, thereby avoiding the cracking of the edge of the stress layer caused by grinding the fiber end face, and optimizing the performance of the polarization-maintaining optical fiber. This document optimizes the original polarization-maintaining optical fiber from the perspective of polarization-maintaining optical fiber stress zone design, and improves the wear resistance of the optical fiber. However, the setting of the refractive index gradient transition layer will affect the birefringence performance of the optical fiber, thereby affecting the precision requirements of the winding, and sacrificing the performance of the optical fiber gyroscope. Summary of the invention

[0008] The purpose of the present invention is to design a polarization-maintaining optical fiber, in particular a panda-type polarization-maintaining optical fiber, which can adapt to grinding and taper processes without sacrificing birefringence performance, so that the optical fiber can be used in the fields of optical fiber gyroscopes and optical fiber devices.

[0009] The research of the present invention mainly includes:

[0010] (1) By appropriately reducing the thermal expansion coefficient of the optical fiber stress zone, the internal stress is reduced, and the risk of optical fiber end face cracking during grinding due to excessive stress in the stress zone is reduced.

[0011] (2) By doping phosphorus in the inner and outer claddings, the viscosity of the inner and outer claddings is reduced, thereby reducing the softening temperature of the inner and outer claddings of the optical fiber, making it suitable for the implementation of the optical fiber taper process. Further, the study controls the doping ratio of P in the inner and outer claddings, on the one hand, to improve the taper experience, on the other hand, to ensure the grinding effect, and meet the taper and grinding process requirements in the application field of optical fiber devices.

[0012] (3) When P-doping the outer cladding, a gradient doping design is used to focus on reducing the viscosity of the quartz near the stress zone, reducing the viscosity difference at the interface between the inner cladding and the outer cladding where the stress zone is located, and enhancing the compatibility of the stress zone and the quartz cladding, which can further reduce the risk of cracking at the edge of the stress zone during optical fiber polishing.

[0013] The specific technical solution adopted by the present invention is: a multi-purpose polarization-maintaining optical fiber, which comprises a core layer, an inner cladding layer, an outer cladding layer and a coating layer from the inside to the outside.

[0014] The core layer is germanium-doped quartz glass with a diameter of D1, a germanium doping molar percentage of 3 to 8 mol.%, and a refractive index n1 of 1.46 to 1.48;

[0015] The inner cladding (2) is phosphorus-doped quartz glass, has a diameter of D2, and a refractive index n2 of 1.4565 to 1.4570;

[0016] The outer cladding (3) is phosphorus-doped quartz glass with a diameter of D3 and a refractive index n3 of 1.4565 to 1.4570;

[0017] Two stress regions (4) are arranged in the inner cladding (2), with a diameter of D4, and are made of boron-doped and fluorine-doped quartz glass, respectively, with a refractive index n4 of 1.34 to 1.48, and the two stress regions (4) are symmetrically arranged on both sides of the core layer (1);

[0018] The refractive index difference between the core layer (1) and the inner cladding layer (2) is n1-n2=0.005-0.020;

[0019] The refractive index difference between the inner cladding (2) and the stress region (4) is n2-n4=0.008-0.015.

[0020] As one of the embodiments of the present application: the boron doping molar percentage of the stress region (4) is 20 to 35 mol%, the fluorine doping molar percentage is 0.5 to 2 mol%, and the fluorine and boron doping molar ratio ∈ (0.025, 0.05); the thermal expansion coefficient of the stress region (4) is 1.5*10 -5 ~5*10 -5 .

[0021] As one of the embodiments of the present application: the phosphorus doping molar concentration of the inner cladding (2) is 0.1-0.8 mol.%, and the softening temperature of the inner cladding (2) is 1500° C.-1600° C.; the phosphorus doping molar concentration of the outer cladding (3) is 0.2-1.6 mol.%, and the softening temperature of the outer cladding (3) is 1600° C.-1700° C. The phosphorus doping molar concentration ratio of the inner cladding (2) and the outer cladding (3) is ∈(1,2).

[0022] As one of the embodiments of the present application: the phosphorus doping of the inner cladding (2) is uniformly doped, and the phosphorus doping molar concentration of the outer cladding (3) is gradually varied along the radial direction, with the doping molar concentration gradually decreasing from the inside to the outside starting from the boundary with the inner cladding (2).

[0023] As one of the embodiments of the present application: the coating layer includes an inner coating layer (5) and an outer coating layer (6), the modulus of the inner coating layer (5) is 0.5MPa to 50MPa, and the modulus of the outer coating layer (6) is 500MPa to 1200MPa.

[0024] As one of the embodiments of the present application: the diameter D1 of the core layer (1) is 4 to 6 μm, the diameter D2 of the inner cladding (2) is 20 to 120 μm, the diameter D3 of the outer cladding (3) is 60 to 125 μm, and the diameter D4 of the stress zone (4) is 12 to 50 μm.

[0025] The above-mentioned polarization-maintaining optical fiber has the following characteristics:

[0026] (1) The core layer is designed to be doped with Ge, and the inner cladding is designed to be doped with P. By controlling the doping ratio, the refractive index difference between the core layer and the inner cladding is maintained at 0.005 to 0.020 to ensure the refractive performance and make the optical fiber have good propagation performance. Under this premise, after the inner cladding is doped with P, the softening temperature of the inner cladding is reduced from 1750°C to about 1550°C, that is, the viscosity of the inner cladding is reduced, so that the optical fiber can match the tapering process of optical fiber devices.

[0027] (2) Stress zone design B and F are co-doped. Both B and F have the function of reducing the refractive index, but their thermal expansion coefficients are different. The thermal expansion coefficient of F is significantly lower than that of B. By controlling the doping ratio of SF6 and BCl3, the refractive index of the stress zone can be adjusted to meet the refractive index difference between the stress zone and the cladding in the range of 0.008 to 0.015. At the same time, the thermal expansion coefficient of the stress zone can also be randomly adjusted to reduce the internal stress of the stress zone, thereby reducing the risk of cracking of the optical fiber end face during grinding due to excessive stress in the optical fiber stress zone, so that the optical fiber can match the grinding process of the optical fiber device.

[0028] (3) The outer cladding is doped with P to reduce the softening temperature of the outer cladding, that is, to reduce the viscosity of the outer cladding. A gradient P doping concentration is preferred. This not only improves the taper operability of the inner and outer claddings, but also reduces the viscosity of the quartz near the stress zone, reduces the viscosity difference between the stress zone and the vicinity, and enhances the compatibility of the stress zone with the outer cladding. This can further reduce the risk of cracking at the edge of the stress zone during optical fiber polishing.

[0029] The method for preparing the above-mentioned multi-purpose polarization-maintaining optical fiber comprises the following steps:

[0030] (1) Mandrel preparation: preparation of germanium-doped quartz preform;

[0031] (2) Preparation of inner and outer cladding: The inner cladding of phosphorus-doped quartz and the outer cladding of phosphorus-doped quartz are formed on the outside of the core in sequence;

[0032] (3) Preparation of stress rods: Preparation of fluorine-boron co-doped quartz preform rods;

[0033] (4) Stress rod assembly: two through holes are drilled in the inner cladding of the preform rod prepared in step (2), and two stress rods prepared in step (3) are inserted into the through holes respectively, with the two stress rods being symmetrically arranged relative to the core rod;

[0034] (5) Drawing the preform into a quartz optical fiber;

[0035] (6) Coating and curing the outer side of the quartz optical fiber to form a coating layer.

[0036] Specifically, step (1) uses in-tube vapor deposition to deposit germanium-doped quartz material in a tube, using a lathe oxyhydrogen flame as a heating source, introducing SiCl4 and GeCl4 into the tube, reacting in the tube to generate silicon dioxide and germanium dioxide particles, which are deposited on the inner wall of the tube using the principle of thermophoresis and vitrified at the same time, and collapse into a solid core rod after the deposition is completed.

[0037] Specifically, step (2) adopts an external vapor deposition method, and SiCl4 and POCl3 raw material vapors are sprayed onto a rotating core rod through a hydrogen-oxygen flame torch. The raw material vapors react in the hydrogen-oxygen flame to generate submicron-sized phosphorus-containing quartz particles that are deposited on the surface of the core rod to form the inner and outer claddings of the core rod. During the deposition process, the flow ratio of POCl3 and SiCl4 is controlled to adjust the phosphorus doping concentration, so as to prepare the inner and outer claddings on the outer layer of the core rod.

[0038] Specifically, step (3) uses in-tube vapor deposition to deposit fluorine-doped and boron-doped quartz materials in the tube, using a lathe hydrogen-oxygen flame as a heating source, and introducing SF6 and BC into the tube. l3 , SiCl4, react in the tube to generate silicon dioxide particles containing boron and fluorine, which are deposited on the inner wall of the tube and vitrified at the same time. After the deposition, the particles collapse into a solid core rod, which is the stress rod. Both fluorine and boron can reduce the refractive index of the stress zone, and the thermal expansion coefficient of fluorine is smaller than that of boron. The refractive index and thermal expansion coefficient of the stress rod can be balanced by adjusting the ratio of fluorine to boron.

[0039] Compared with the prior art, the advantages of the present invention are:

[0040] 1. The polarization-maintaining optical fiber of the present invention can adapt to the grinding and taper processes in the field of optical fiber device manufacturing, and can also adapt to the ring winding process in the field of optical fiber gyroscope manufacturing, thus realizing multiple uses of a polarization-maintaining optical fiber.

[0041] 2. The polarization-maintaining optical fiber of the present invention can optimize the doping ratio of fluorine and boron in the stress zone, thereby adjusting and optimizing the thermal expansion coefficient of the stress zone under the condition that the refractive index of the polarization-maintaining optical fiber remains unchanged, and can take into account the process requirements of different application devices.

[0042] 3. The polarization-maintaining optical fiber of the present invention, through the segmented phosphorus-doped design of the inner and outer claddings, can effectively reduce the viscosity of the optical fiber silicon layer, reduce the melting temperature, and improve the operability of the optical fiber taper processing process while ensuring that the optical fiber light propagation conditions are not affected. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a schematic cross-sectional view of the polarization-maintaining optical fiber of the present invention;

[0044] Figure 2 Schematic diagram of the refractive index profile of the polarization-maintaining optical fiber of the present invention;

[0045] In the figure, there are core layer 1, inner cladding layer 2, outer cladding layer 3, stress zone 4, inner coating layer 5, and outer coating layer 6. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with the accompanying drawings. The embodiments are exemplary and are intended to be used to explain the present invention, but should not be understood as limiting the present invention. The text description in this embodiment corresponds to the accompanying drawings, and the description of the embodiment should not be understood as limiting the scope of protection of the present invention.

[0047] like Figure 1 As shown, the cross-sectional structure of the polarization-maintaining optical fiber in the embodiment of the present invention comprises, from the inside to the outside, a core layer 1, an inner cladding 2, an outer cladding 3 and a coating layer. The core layer 1 is germanium-doped quartz glass with a diameter of D1 and a refractive index of n1; the inner cladding 2 is phosphorus-doped quartz glass with a diameter of D2 and a refractive index of n2; the outer cladding 3 is phosphorus-doped quartz glass with a diameter of D3 and a refractive index of n3; two stress regions 4 are arranged in the inner cladding 2, with a diameter of D4, which are boron-doped and fluorine-doped quartz glass, respectively, with a refractive index of n4, and the two stress regions 4 are symmetrically arranged on both sides of the core layer 1; the refractive index difference between the core layer 1 and the inner cladding 2 is n1-n2=0.005-0.020; the refractive index difference between the inner cladding 2 and the stress region 4 is n2-n4=0.008-0.015.

[0048] Table 1 is a comparison of parameters of Example 4 and Comparative Examples 1-3 obtained based on the above cross-sectional structure

[0049] Table 1

[0050]

[0051]

[0052] The polarization-maintaining optical fiber of this embodiment reduces the softening temperature of the silicon layer from 1750°C to about 1550°C by adding POCl3 reactive doping during the deposition process of the inner cladding SiO2, which can effectively improve the deposition efficiency of the silicon layer and improve the applicability of users in the optical fiber tapering process.

[0053] In the polarization-maintaining optical fiber of this embodiment, the stress layer is co-doped with fluorine and boron, and both B and F have the effect of reducing the refractive index, but their thermal expansion coefficients are different. By controlling the doping ratio of SF6 and BCl3, the refractive index difference between the stress zone and the cladding is controlled within a range of 0.008 to 0.015, which can also optimize the thermal expansion coefficient of the stress zone, reduce internal stress, and reduce the risk of end face cracking during grinding due to excessive stress in the optical fiber stress zone.

[0054] As an implementation method, the production process of polarization-maintaining optical fiber adopts the following steps:

[0055] Step 1, core rod preparation: The silicon germanium material is deposited in the tube mainly by in-tube vapor deposition. The lathe oxyhydrogen flame is used as the heating source. High-purity silicon tetrachloride and germanium tetrachloride in different proportions are introduced into the front end to react and generate silicon dioxide and germanium dioxide particles, which are deposited on the inner wall of the substrate tube by the principle of thermophoresis and vitrified at the same time. After the deposition is completed, it collapses into a solid core rod.

[0056] Step 2, preparation of inner and outer cladding: mainly using external vapor deposition method, while the flame is sprayed onto the core rod through a hydrogen-oxygen flame blowtorch, raw material vapors such as SiCl4 and POCl3 are also passed through the blowtorch. The raw material vapor reacts in the hydrogen-oxygen flame to generate submicron-sized phosphorus-containing quartz particles that are deposited on the surface of the core rod to form the inner and outer cladding of the core rod. In this step, the phosphorus doping ratio of the inner cladding is greater than or equal to that of the outer cladding. Under the premise of not affecting the optical fiber light guiding conditions, the specific flow rate can be adjusted according to specific process requirements by precisely controlling the flow of POCl3 and SiCl4. When the inner cladding is deposited, the typical concentration of POCl3 and SiCl4 is about 1:3, and the typical value of the phosphorus doping concentration ratio of the inner and outer cladding is controlled at about 3:2. It should be noted that the size of the inner cladding needs to cover part of the stress zone during deposition, such as Figure 1 The purpose of this design is to ensure that the stress zone is located in the inner cladding area with a relatively low softening temperature, which can reduce the risk of cracking during grinding of the edge of the stress zone.

[0057] Step 3, stress rod preparation: mainly use the method of in-tube vapor deposition to deposit fluorine, boron and silicon materials in the tube, use the lathe hydrogen-oxygen flame as the heating source, and introduce different proportions of high-purity SF6, BCl3, and SiCl4 into the front end to react and generate silicon dioxide particles containing boron and phosphorus, which are deposited on the inner wall of the base tube and vitrified at the same time. After the deposition is completed, it collapses into a solid core rod. In this step, the main purpose of fluorine and boron is to reduce the refractive index. Since the refractive indexes of the two raw materials are similar, the thermal expansion coefficient of boron is greater than that of fluorine. The refractive index and thermal expansion coefficient of the stress rod are controlled by adjusting and optimizing the ratio of fluorine to boron to ensure the abrasion resistance of the final optical fiber stress zone. In the process of fluorine and boron co-doping, in order to avoid the situation where the thermal expansion coefficient of the stress zone is too low due to excessive fluorine doping, its flow rate needs to be accurately controlled according to the process requirements. The typical value of the concentration ratio of fluorine and boron can be controlled to be about 1:30.

[0058] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.

Claims

1. A multi-purpose polarization-maintaining optical fiber, characterized in that: From the inside to the outside, they are the core layer (1), the inner cladding layer (2), the outer cladding layer (3) and the coating layer. The core layer (1) is germanium-doped quartz glass, with a diameter of D1, a germanium doping molar percentage of 3-8 mol.%, and a refractive index n1 of 1.46-1.48; The inner cladding (2) is phosphorus-doped quartz glass, has a diameter of D2, and a refractive index n2 of 1.4565-1.4570; The outer cladding (3) is phosphorus-doped quartz glass with a diameter of D3 and a refractive index n3 of 1.4565-1.4570; Two stress regions (4) are arranged in the inner cladding (2), have a diameter of D4, are made of boron- and fluorine-doped quartz glass, and have a refractive index n4 of 1.34 to 1.48, and the two stress regions (4) are symmetrically arranged on both sides of the core layer (1); The refractive index difference between the core layer (1) and the inner cladding layer (2) is n1-n2=0.005-0.020; The refractive index difference between the inner cladding (2) and the stress region (4) is n2-n4=0.008-0.

015.

2. The multi-purpose polarization-maintaining optical fiber according to claim 1, characterized in that: The boron doping molar percentage of the stress region (4) is 20-35 mol.%, the fluorine doping molar percentage is 0.5-2 mol.%, and the fluorine and boron doping molar ratio ∈ (0.025, 0.05); the thermal expansion coefficient of the stress region (4) is 1.5×10 -5 ~5×10 -5 .

3. The multi-purpose polarization-maintaining optical fiber according to claim 2, characterized in that: The phosphorus doping molar concentration of the inner cladding (2) is 0.1-0.8 mol.%, and the softening temperature of the inner cladding (2) is 1500°C-1600°C; the phosphorus doping molar concentration of the outer cladding (3) is 0.2-1.6 mol.%, and the softening temperature of the outer cladding (3) is 1600°C-1700°C; the phosphorus doping molar concentration ratio of the inner cladding (2) to the outer cladding (3) is ∈(1, 2).

4. The multi-purpose polarization-maintaining optical fiber according to claim 3, characterized in that: The phosphorus doping of the inner cladding (2) is uniformly doped, and the phosphorus doping molar concentration of the outer cladding (3) is gradually varied along the radial direction, with the doping molar concentration gradually decreasing from the inside to the outside starting from the boundary with the inner cladding (2).

5. The multi-purpose polarization-maintaining optical fiber according to claim 1, characterized in that: The coating layer comprises an inner coating layer (5) and an outer coating layer (6), the modulus of the inner coating layer (5) is 0.5 MPa to 50 MPa, and the modulus of the outer coating layer (6) is 500 MPa to 1200 MPa.

6. The multi-purpose polarization-maintaining optical fiber according to claim 1, characterized in that: The diameter D1 of the core layer (1) is 4 to 6 μm, the diameter D2 of the inner cladding layer (2) is 20 to 120 μm, the diameter D3 of the outer cladding layer (3) is 60 to 125 μm, and the diameter D4 of the stress zone (4) is 12 to 50 μm.

7. A method for preparing the multi-purpose polarization-maintaining optical fiber according to any one of claims 1 to 6, characterized in that: The following steps are included (1) Core rod preparation: preparation of germanium-doped quartz preform; (2) Preparation of inner and outer cladding: The inner cladding of phosphorus-doped quartz and the outer cladding of phosphorus-doped quartz are formed on the outside of the core rod in sequence to obtain a preformed rod; (3) Preparation of stress rods: Preparation of fluorine-boron co-doped quartz preform rods; (4) Stress rod assembly: Drill two through holes in the inner cladding of the preform rod prepared in step (2), take two stress rods prepared in step (3) and insert them into the through holes respectively, with the two stress rods being symmetrically arranged relative to the core rod; (5) Drawing the preform into a quartz optical fiber; (6) Coating and curing the outer side of the quartz optical fiber to form a coating layer.

8. The preparation method according to claim 7, characterized in that: Step (1) uses in-tube vapor deposition to deposit germanium-doped quartz material in a tube, using a lathe hydrogen-oxygen flame as a heating source, and introducing SiCl4 and GeCl4 into the tube to react in the tube to generate silicon dioxide and germanium dioxide particles, which are deposited on the inner wall of the tube by the principle of thermophoresis and vitrified at the same time. After the deposition is completed, the material collapses into a solid core rod.

9. The preparation method according to claim 7, characterized in that: Step (2) adopts an external vapor deposition method, and sprays SiCl4 and POCl3 raw material vapor onto a rotating core rod through a hydrogen-oxygen flame torch. The raw material vapor reacts in the hydrogen-oxygen flame to generate submicron-sized phosphorus-containing quartz particles that are deposited on the surface of the core rod to form the inner and outer cladding of the core rod. During the deposition process, the flow ratio of POCl3 and SiCl4 is controlled to adjust the phosphorus doping concentration, so as to prepare the inner and outer cladding on the outer layer of the core rod.

10. The preparation method according to claim 7, characterized in that: Step (3) uses in-tube vapor deposition to deposit fluorine-doped and boron-doped quartz materials in the tube. Using a lathe hydrogen-oxygen flame as a heating source, SF6, BCl3, and SiCl4 are introduced into the tube. Silicon dioxide particles containing boron and fluorine are generated by reaction in the tube and deposited on the inner wall of the tube and vitrified at the same time. After the deposition is completed, the silicon dioxide particles collapse into a solid core rod, which is the stress rod. Both fluorine and boron can reduce the refractive index of the stress zone. The thermal expansion coefficient of fluorine is smaller than that of boron. The refractive index and thermal expansion coefficient of the stress rod are balanced by adjusting the ratio of fluorine to boron.

Citation Information

Patent Citations

  • Manufacture method of low-stress polarization maintaining optical fibre applied to coupling

    CN103145349A

  • Anti-cracking panda type polarization maintaining optical fiber

    CN106291807A

  • Panda type polarization maintaining optical fiber

    CN101825738A

  • Ytterbium-doped optical fiber, fiber laser, and fiber amplifier

    CN101999197A

  • Double-clad optical fiber

    CN103323910A